Supervision of clinical assessment: The Multilevel Assessment Supervision and Training (MAST) approach. Issue 1 (2nd January 2016) - Tawfik, Saneya H.; Landoll, Ryan R.; Blackwell, Laura S.; Taylor, Cortney J.; Hall, Daniel L.
Abstract : Supportive and effective clinical supervision is imperative to the training and development of assessment skills in clinical psychology. This article presents the development of the Multilevel Assessment Supervision and Training approach, a clinic-based method to supervision of assessment. This approach utilizes advanced predoctoral students to serve as peer supervisors for beginning predoctoral trainees conducting psychoeducational assessments. It offers several advantages, providing a peer mentoring supervisory experience during graduate education, improving the training experience and oversight for beginning trainees, and improving service delivery. Satisfaction ratings were collected from graduate trainees and their peer supervisors who support the utility of this approach.